Cysteine Substitution and Calcium-Binding Mutations in FBN1 cbEGF-Like Domains Are Associated With Severe Ocular Involvement in Patients With Congenital Ectopia Lentis - Zhang, Min; Chen, Zexu; Chen, Tianhui; Sun, Xiaodong; Jiang, Yongxiang (Frontiers in Cell and Developmental Biology, 2022)
Purpose: To investigate the clinical manifestations of congenital ectopia lentis (CEL) in patients with fibrillin (FBN1) calcium-binding epidermal growth factor (cbEGF)-like mutations. Design: Retrospective cohort study. Methods: Consecutive 68 CEL probands with FBN1 cbEGF-like mutations were recruited, mostly comprising Marfan syndrome (MFS) patients. Patients were classified into the cysteine group (n = 43), calcium (Ca2+)-binding group (n = 13) or the others (n = 12) according to their genotypes. Ocular biometrics, morbidities and visual performance were compared among different mutation groups. Linear regression was used to evaluate the risk factors for axial length (AL) elongation. Results: With age-adjustment, cysteine substitution and Ca2+-binding mutations positively contributed to AL elongation (standardized coefficient: 0.410 and 0.367, P = 0.008 and 0.017, respectively). In addition, cataract formation was more frequently detected in patients with Ca2+-binding mutations (observed n = 3, expected n = 1.0; P = 0.036). Patients with cysteine substitutions had the poorest preoperative visual acuity among the three groups (P = 0.012) and did not recover as well as other patients. More MFS diagnoses were made in patients with cysteine substitutions (observed n = 16, expected n = 12.6), while ectopia lentis syndrome was detected more often in patients with cbEGF-like mutations out of the functional regions (observed n = 6, expected n = 2.5; P = 0.023). Conclusion: Compared with patients with cbEGF-like mutations out of functional regions, patients with cysteine substitutions or Ca2+-binding mutations had longer ALs with age adjustment, poorer ocular involvement, visual performance, and systematic manifestations.